2022
DOI: 10.1111/jocd.15510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a live Cutibacterium acnes subspecies defendens strain XYCM42 and clinical assessment as a topical regimen for general skin health and cosmesis

Abstract: Background When formulating topical products to treat skin diseases and addressing general skin health and cosmesis, most of the focus has traditionally been placed on how any given ingredient may impact the structure, function, and health of human skin elements. However, recent research is beginning to highlight the importance of the skin microbiome in relation to certain skin conditions and general cosmesis. Cutibacterium acnes is one of the most prolific skin‐specific bacterial species. Research has shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Despite there being no definitive evidence that acne is in any way communicable via microbial transference or that microbial over-proliferation is connected to developing acne or the severity of the disease state, these ideas seem to persist. 7,[25][26][27][28][29] The common misperception that C. acnes is solely responsible for acne or that microneedling could spread C. acnes across the face has likely hindered research into investigating such as a potential treatment for acne. However, as acne is a multi-factorial disease state involving the hyperkeratinization of the stratum corneum, which blocks the normal flow of sebum from the follicle, it makes sense that initiation of local skin remodeling via transdermal microneedling (involving rapid turnover of the epidermis and stratum corneum) would allow for relief of acneic symptoms during the remodeling process.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite there being no definitive evidence that acne is in any way communicable via microbial transference or that microbial over-proliferation is connected to developing acne or the severity of the disease state, these ideas seem to persist. 7,[25][26][27][28][29] The common misperception that C. acnes is solely responsible for acne or that microneedling could spread C. acnes across the face has likely hindered research into investigating such as a potential treatment for acne. However, as acne is a multi-factorial disease state involving the hyperkeratinization of the stratum corneum, which blocks the normal flow of sebum from the follicle, it makes sense that initiation of local skin remodeling via transdermal microneedling (involving rapid turnover of the epidermis and stratum corneum) would allow for relief of acneic symptoms during the remodeling process.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Additionally, recent research has shown that certain strains of C . acnes are healthy for skin and can contribute to benefits such as antioxidant activity, anti‐inflammatory activity, and upregulation of genes involved in skin barrier homeostasis 7 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations